Addressing knowledge, attitude and practice gaps for effective dengue management strategies in Indonesia - Ari Prayitno; Mei Neni Sitaresmi; Bachti Alisjahbana; Bachti Alisjahbana; Carolina Halim; Fauchil Wardati; Mentari Yudiansyach; Sri Rezeki Hadinegoro (Frontiers in Public Health)
BackgroundDengue is a significant public health issue in Indonesia, facing a substantial year-round disease burden and rising incidence. However, comprehensive assessments of Knowledge, Attitudes, and Practices (KAP) regarding dengue in the Indonesian adult population are limited. This study provides one of the first comprehensive evaluations of KAP in Indonesia, aiming to inform integrated dengue management programs.MethodsThis study utilized data from the larger GEMKAP study, which covered seven countries, including Indonesia. The GEMKAP study was a cross-sectional electronic survey conducted in September and October 2022, targeting adults aged 21 to 60, recruited through email invitations from an existing web-based panel. The survey, consisting of 35 questions, was developed based on existing dengue KAP studies and was translated into Bahasa Indonesia.ResultsAnalysis of 600 Indonesian responses revealed higher levels of Attitudes (65%) and Practices (56%) compared to Knowledge (46%). Most respondents correctly identified dengue transmission through Aedes mosquitoes (85%) and mosquito breeding grounds (98%); however, awareness of dengue serotypes (48%) and multiple infection risks (50%) was lower. Out of the dengue prevention methods practiced, draining and covering water containers was rated the safest and most effective (8.4 and 8.1, respectively, on a scale from 0 to 10). In comparison, dengue vaccination was perceived as generally safe and effective (7.6 and 7.7, respectively, on a scale from 0 to 10). Willingness to receive dengue vaccines was moderate (51%), with 60% unaware of vaccine availability. Fear of side effects (18%) was the most common reason for moderate willingness to vaccinate. Respondents preferred search engines (88%) and social media (85%) as sources to search health information, with doctors being the most trusted stakeholder to receive health information from (94%). The most favored dengue management strategy was combining vaccination with education and vector control (42%).ConclusionThe KAP assessment identified strengths and gaps in dengue awareness and practices among Indonesians. The gaps identified from the KAP results underscore the need for an integrated approach combining vector control, vaccination, and education. As the most trusted stakeholders, HCPs can play a key role in supporting the effective implementation of dengue management strategies.